2013
DOI: 10.1016/j.chom.2013.08.015
|View full text |Cite
|
Sign up to set email alerts
|

The Interferon-Inducible MxB Protein Inhibits HIV-1 Infection

Abstract: The interferon-inducible myxovirus resistance (Mx) proteins play important roles in combating a wide range of virus infections. MxA inhibits many RNA and DNA viruses, whereas the antiviral activity of MxB is less well established. We find that human MxB inhibits HIV-1 infection by reducing the level of integrated viral DNA. Passaging HIV-1 through MxB-expressing cells allowed the evolution of a mutant virus that escapes MxB restriction. HIV-1 escapes MxB restriction by mutating the alanine residue at position … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

21
398
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 309 publications
(423 citation statements)
references
References 61 publications
21
398
1
3
Order By: Relevance
“…These experiments suggested that MxB does not contribute to the ability of IFN-␣-treated cells to block HIV-1 infection. This is in agreement with the following reported findings suggesting that MxB is not the restriction factor responsible for the block to HIV-1 observed in IFN-␣-treated human cells: (i) MxB is an HIV-1 restriction factor that blocks HIV-1 infection after reverse transcription (9,22,23,27,29), and (ii) treatment of human cells with IFN-␣ imposes a restriction on HIV-1 before the occurrence of reverse transcription (35). Next, we investigated the HIV-1 life cycle stage at which the block imposed by IFN-␣-treated THP-1 cells occurs.…”
Section: Fig 5 Ifn-␣ Treatment Of Thp-1 Cells Prevents the Formation supporting
confidence: 82%
See 4 more Smart Citations
“…These experiments suggested that MxB does not contribute to the ability of IFN-␣-treated cells to block HIV-1 infection. This is in agreement with the following reported findings suggesting that MxB is not the restriction factor responsible for the block to HIV-1 observed in IFN-␣-treated human cells: (i) MxB is an HIV-1 restriction factor that blocks HIV-1 infection after reverse transcription (9,22,23,27,29), and (ii) treatment of human cells with IFN-␣ imposes a restriction on HIV-1 before the occurrence of reverse transcription (35). Next, we investigated the HIV-1 life cycle stage at which the block imposed by IFN-␣-treated THP-1 cells occurs.…”
Section: Fig 5 Ifn-␣ Treatment Of Thp-1 Cells Prevents the Formation supporting
confidence: 82%
“…Genetic evidence suggested that the HIV-1 capsid is the determinant for the ability of MxB to block HIV-1 infection (9,22,23). In agreement with these findings, we recently demonstrated that MxB binds to the HIV-1 capsid and correlated the ability of MxB to block HIV-1 infection with inhibition of uncoating (24).…”
supporting
confidence: 75%
See 3 more Smart Citations